GPR126 regulates colorectal cancer cell proliferation by mediating HDAC2 and GLI2 expression. Issue 5 (19th March 2021) - Cui, Hengxiang; Yu, Wenjie; Yu, Minhao; Luo, Yang; Yang, Mingming; Cong, Ruochen; Chu, Xin; Gao, Ganglong; Zhong, Ming
Abstract: The G‐protein‐coupled receptor 126 (GPR126) may play an important role in tumor development, although its role remains poorly understood. We found that GPR126 had higher expression in most colorectal cancer cell lines than in normal colon epithelial cell lines, and higher expression levels in colorectal cancer tissues than in normal adjacent colon tissues. GPR126 knockdown induced by shRNA inhibited cell viability and colony formation in HT‐29, HCT116, and LoVo cells, decreased BrdU incorporation into newly synthesized proliferating HT‐29 cells, led to an arrest of cell cycle progression at the G1 phase in HCT‐116 and HT‐29 cells, and suppressed tumorigenesis of HT‐29, HCT116, and LoVo cells in nude mouse xenograft models. GPR126 knockdown engendered decreased transcription and translation of histone deacetylase 2 (HDAC2), previously implicated in the activation of GLI1 and GLI2 in the Hedgehog signaling pathway. Ectopic expression of HDAC2 in GPR126‐silenced cells restored cell viability and proliferation, GLI2 luciferase reporter activity, partially recovered GLI2 expression, and reduced the cell cycle arrest. HDAC2 regulated GLI2 expression and, along with GLI2, it bound to the PTCH1 promoter, as evidenced by a chip assay with HT‐29 cells. Purmorphamine, a hedgehog agonist, largely restored the cell viability and expression of GLI2 proteins in GPR126‐silenced HT‐29 cells, whereas GANT61, a hedgehog inhibitor, further enhanced the GPR126 knockdown‐induced inhibitory effects. Our findings demonstrate that GPR126 regulates colorectal cancer cell proliferation by mediating the expression of HDAC2 and GLI2, therefore it may represent a suitable therapeutic target for colorectal cancer treatment. Abstract : GLI2 binding with HDAC2 to the PTCH1 promoter is regulated by HDAC2 and its expression recovery restores cell viability in GPR126‐silenced cells. A, Western blotting of HDAC2 and GLI2 protein levels in NC‐ and HDAC2‐shRNA‐infected HT‐29 cells. β‐actin was used as a loading control. B, Chromatin from HT‐29 cells was immunoprecipitated with anti‐HDAC2 antibodies and then eluted and immunoprecipitated again with normal mouse IgG(IgG) or anti‐Gli2(GLI2 Ab). Eluted DNA was PCR‐amplified using PTCH1 and GAPDH primers (B1). Quantitative PCR(qPCR) was used to examine the abundance of eluted DNA from B1, with the DNAs from input control as the internal control (B2). C, Ectopic expression of HDAC2 in GPR126‐silenced cells restores transcription activity of GLI2 promoter (Gli2‐Luc). NC or Sh1, cell infected by control virus or GPR126 shRNA virus; pGL3, empty luciferase vector; Gli2‐Luc, luciferase vector with Gli2 promoter; zs‐HDAC2, HDAC2 ectopic expression construct; zs, empty vector for cloning HDAC2 expression vector; '‐', not used in co‐transfection; '+', used in co‐transfection. D‐E, the effect of Purmorphamine (hedgehog agonist) and GANT61 (GLI2 inhibitor), at indicated concentration, on cell viability and GLI2 protein expression in indicate colorectal cancer cells. DMSO, the solvent of Purmorphamine and GANT61. β‐actin was used as a loading control. F, Diagram illustrating the putative mechanisms of GPR126 function in colorectal cancer cells. GPR126 regulates SMO, GLI1, and HDAC2 expression (GSE106696). GLI1 and GLI2, as the downstream components of GPR126 signaling, regulate the expression of hedgehog (HH) target genes, including PTCH1, regulating tumor growth. HDAC2 is regulated by GPR126 regulated HDAC2, mediating GLI2 expression, and binds with GLI2 to the PTCH1 promoter or other promoters of HH target genes. The dotted line indicating 'Not reported in this article'; solid line indicating 'Has support in this article'; '?' meaning 'through unknown mechanism'.